The Electrosynthetic Toolkit for Stereoselective Alkene 1,2-Difunctionalization - Wanderley, Taciano Antonio Santos; Crisenza, Giacomo Ercole Martino (Synlett, 2025)
The asymmetric 1,2-difunctionalization of alkenes stands as one of the swiftest approaches to turn ubiquitous C(sp2)-feedstocks into C(sp3)-rich chiral fine chemicals. State-of-the-art transition metal-catalyzed protocols are efficient, selective, and robust; however, they are often limited in alkene scope, functional group tolerance, and are only applicable to specialized systems. Recently, the use of synthetic electrochemistry has provided effective solutions to these challenges, fostering the development of more general, selective, and sustainable variants. In this Synpacts, we will survey selected literature examples showcasing how electrosynthetic tools have been instrumental in enabling the design of innovative diastereo- and enantioselective alkene 1,2-difunctionalization reactions. These seminal contributions have inspired us to conceive a complementary “Sew & Cut” strategy—combining the generality and selectivity of pericyclic 1,3-dipolar cycloadditions with the complexity-generating ability of radical reactivity.
Keywords: Electrosynthesis; Alkene functionalization; Radical reactivity; Asymmetric processes; 1,3-Dipolar cycloadditions